Country-level determinants of gender differences in major depression and alcohol use disorder: Daniel Hagen. (25th October 2022) - Hagen, D; Goldmann, E; Ompad, DC; Bambra, C
Abstract: Background: Major depressive disorder (MDD) and alcohol use disorder (AUD) are leading causes of disease burden in Europe, with MDD disproportionately affecting women and AUD being more prevalent among men. However, it is unclear how country-level political and socio-cultural characteristics contribute to gender differences in these conditions. Methods: Data for 30, 416 participants from 16 countries were obtained from the 2014 European Social Survey. Depressive symptoms were ascertained using the 8-item CES-D scale, and alcohol use was assessed with items on past-year alcohol use frequency and quantity, as well as frequency of heavy episodic drinking. Country-level data for attitudes to gender equality, needs-adjusted public social expenditure, and other covariates came from the 2012 International Social Survey Programme and the OECD. Modified Poisson and linear regression with log link examined additive and multiplicative interactions of country-level characteristics with gender for MDD, AUD, and their specific symptoms/dimensions. Results: Public social expenditure was not associated with gender differences in MDD (CES-D>10), but with greater differences in the prevalence of the loneliness and sadness symptoms; support for gender equality was associated with smaller differences in loneliness (p < 0.05). For AUD, there was evidence of increased alcohol use frequency and quantity among women, and decreased frequency and quantity among men associated with support for gender equality, resulting in lower gender differences in predicted probabilities (from 23% to 5% across exposure levels; p < 0.001). Heavy episodic drinking was strongly positively associated with support for gender equality among women (p < 0.001), but not among men. Conclusions: Country-level characteristics appear to exert differential impact on the prevalence of AUD and certain psychological symptoms of MDD among men and women in Europe. Pending replication, future research should examine underlying mechanisms. Key messages: Country-level characteristics appear to influence the magnitude of gender differences in prevalent alcohol use disorder and certain psychological symptoms of major depression across Europe. Favourable country-level attitudes towards gender equality appear to be associated with lower overall prevalence of alcohol use disorder, but higher prevalence among women.